2018
DOI: 10.1002/smll.201804321
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Reaction Generates Biomimic Nanominerals with Superior Bioactivity

Abstract: In vivo mineralization is a multistep process involving mineral‐protein complexes and various metastable compounds in vertebrates. In this complex process, the minerals produced in the mitochondrial matrix play a critical role in initiating extracellular mineralization. However, the functional mechanisms of the mitochondrial minerals are still a mystery. Herein, an in vitro enzymatic reaction strategy is reported for the generation of biomimic amorphous calcium phosphate (EACP) nanominerals by an alkaline phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…We think that the activation of platelets is related to the large amount of ADP molecules in EACPNs. In our previous study, we revealed the content of ADP molecules in EACPNs by a high-performance liquid chromatography (HPLC) method, which indicated that there is approximately 0.15 g of ADP molecules in each gram of EACPNs ( Jiang et al, 2018 ). It has been reported that ADP, as a soluble agonist released by activated cells, can trigger platelet activation through GPCRs, thereby promoting coagulation formation ( Yun et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We think that the activation of platelets is related to the large amount of ADP molecules in EACPNs. In our previous study, we revealed the content of ADP molecules in EACPNs by a high-performance liquid chromatography (HPLC) method, which indicated that there is approximately 0.15 g of ADP molecules in each gram of EACPNs ( Jiang et al, 2018 ). It has been reported that ADP, as a soluble agonist released by activated cells, can trigger platelet activation through GPCRs, thereby promoting coagulation formation ( Yun et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…EACPNs were prepared via an enzymatic reaction strategy reported in our previous work ( Jiang et al, 2018 ). Briefly, CaCl 2 (66.0 mg) was dissolved into deionized water (30.0 ml), and then aqueous solution (30.0 ml) containing Na 2 ATP (110.0 mg) was added drop-wise into the above Ca 2+ solution under magnetic stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amorphous calcium phosphate (ACP) plays an important role in the biomineralization of bone, teeth, and other tissues, serving as a precursor for apatite minerals [ [1] , [2] , [3] , [4] , [5] ]. Previous studies revealed that ACP was found intracellularly in mineralizing cells, especially as mineral granules in mitochondria [ 6 , 7 ], which can be transported in matrix vesicles via lysosomes and secreted by exocytosis to the extracellular matrix for biomineralization [ 8 ]. The C-terminal end of collagen molecules with a positive net charge promoted the infiltration of these ACP granules to collagen fibrils [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic CaP-based biomaterials have demonstrated excellent biodegradability, bioactivity and osteoconductivity, and are widely used for bone-defect repair and prevention of bone-loss diseases (e.g. osteoporosis) [ 8–12 ]. The detailed composition of CaP in natural bones is far more complicated, since it usually contains other ions that substitute the original CaP structure such as − , Mg 2+ and Na + [ 2 ].…”
Section: Introductionmentioning
confidence: 99%